Development of a Canva-based e-booklet for geometry learning in elementary school students - Hasibuan, Eunike Gracella Efrata; Destrinelli, Destrinelli; Zahyuni, Violita (Asatiza: Jurnal Pendidikan, 2025)
This study aims to develop an e-booklet as an instructional medium designed using Canva to enhance elementary school students’ understanding of geometric elements. The e-booklet facilitates visualization and spatial comprehension of geometric concepts, such as points, lines, and three-dimensional shapes, which students often find challenging to grasp. The study employed a Research and Development (R&D) approach using the ADDIE model, encompassing the stages of analysis, design, development, implementation, and evaluation. Validation was conducted by subject matter, media, and language experts, and the e-booklet was tested on small and large groups. The validation results indicated high levels of validity, with average scores of 4.7 for content, 4.8 for media, and 4.8 for language. Practicality was also rated highly, with an average score of 5 based on teachers’ evaluations and positive feedback from students, demonstrating improved understanding of geometric concepts. The e-booklet effectively delivers geometric concepts visually and interactively, serving as an alternative and effective learning medium. This study concludes that the Canva-based e-booklet can create an engaging learning environment and support teachers in the instructional process. Further development is recommended to enhance its effectiveness in teaching other mathematical topics.